2020
DOI: 10.1021/acs.molpharmaceut.0c00281
|View full text |Cite
|
Sign up to set email alerts
|

Surfactin Ameliorated the Internalization and Inhibitory Performances of Bleomycin Family Compounds in Tumor Cells

Abstract: The cationic glycopeptide bleomycin (BLM) is a broad-spectrum chemotherapy drug clinically applied to treat various malignant tumors. The poor cell membrane permeability of BLM, which is prone to high dose usage and may consequently induce dose-dependent lung toxicity, is a sticking point to limit clinical applications of BLM. As a commercial biosurfactant, the anionic lipopeptide surfactin (SF) is well known for its potent ability to disturb membranes and widely applied in cosmetic area as a permeabilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…The in vitro antitumor activities of β‐RUB ( 1 ), γ‐RUB ( 2 ), RUB CA1 ( 3 ), and β‐RUB acid ( 7 ) were respectively evaluated against four different human cancer cell lines, including the nonsmall cell lung cancer cell line A549, the liver hepatocellular carcinoma HepG2, the cervical cancer cell line Hela, and the colon tumor cell line Caco‐2 (Xiong et al, 2020). During the assays, the distinct purple precipitate of β‐RUB ( 1 ) or γ‐RUB ( 2 ) was clearly observed in serum under high concentrations (data not shown), therefore the relative solubilities of four compounds in serum were first determined based on the quantitative HPLC analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro antitumor activities of β‐RUB ( 1 ), γ‐RUB ( 2 ), RUB CA1 ( 3 ), and β‐RUB acid ( 7 ) were respectively evaluated against four different human cancer cell lines, including the nonsmall cell lung cancer cell line A549, the liver hepatocellular carcinoma HepG2, the cervical cancer cell line Hela, and the colon tumor cell line Caco‐2 (Xiong et al, 2020). During the assays, the distinct purple precipitate of β‐RUB ( 1 ) or γ‐RUB ( 2 ) was clearly observed in serum under high concentrations (data not shown), therefore the relative solubilities of four compounds in serum were first determined based on the quantitative HPLC analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The antitumor activity of β‐RUB ( 1 ), γ‐RUB ( 2 ), RUB CA1 ( 3 ), and β‐RUB acid ( 7 ), as well as the positive control BLM‐sulfate, were respectively evaluated in four different human tumor cell lines (A549, HepG2, Caco‐2, and Hela) by the standard CCK‐8 assay (Xiong et al, 2020). Briefly, cells were seeded in 96‐well plates with 4 × 10 3 cells per well and stabilized for 24 h. Then cells were treated with a certain agent at different concentrations in 100 µl media per well.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, surfactin was used to enhance the drug‐delivering capacity of bleomycin (BLM). The addition of surfactin is reported to have enhanced the efficiency of receptor‐mediated endocytosis of BLM by destabilization of biological membranes, while keeping the resulting cytotoxicity of the formulation low, owing to the higher safety of surfactin in comparison with other surfactants (Xiong et al, 2020). Similarly, it was observed that almost 80% of surfactin‐treated wounds were closed, indicating that surfactin could also be used as an affordable wound healing drug (Yan et al, 2020).…”
Section: Biosurfactants As Potential Emulsifiers For Green Nanoemulsionsmentioning
confidence: 99%